Down‐regulation of POTEG predicts poor prognosis in esophageal squamous cell carcinoma patients. Issue 7 (6th April 2018) - Wang, Ling; Li, Mengqing; Zhan, Yuting; Ban, Xiaojiao; Zeng, Tingting; Zhu, Yinghui; Yun, Jingping; Guan, Xin‐Yuan; Li, Yan
Abstract : POTE ankyrin domain family, member G ( poteg ) belongs to POTE family. The POTE family is composed of many proteins which are very closely related and expressed in prostate, ovary, testis, and placenta. Some POTE paralogs are related with some cancers. Here we showed that down‐regulation of POTEG was detected in about 60% primary esophageal squamous cell carcinoma (ESCC) tumor tissues. Clinical association studies determined that POTEG down‐regulation was significantly correlated with tumor differentiation, lymph nodes metastasis and TNM staging. Kaplan‐Meier analysis determined that POTEG down‐regulation was associated with poorer clinical outcomes of ESCC patients ( P  = 0.026). Functional studies showed that POTEG overexpression could suppress tumor cell growth and metastasis capacity in vitro and in vivo. Molecular analyses revealed that POTEG downregulated CDKs, leading to subsequent inhibition of Rb phosphorylation, and consequently arrested Cell Cycle at G1/S Checkpoint. POTEG overexpression induced apoptosis by activating caspases and PARP, and regulating canonical mitochondrial apoptotic pathways. On the other side, POTEG inhibited epithelial‐mesenchymal transition and suppressed tumor cell metastasis. In conclusion, our study reveals a functionally important control mechanism of POTEG in esophageal cancer pathogenesis, suggesting potential use in the ESCC intervention and therapeutic strategies.